Effectiveness of Traffic Enforcer at Barangay Novaliches Proper in Quezon City.: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Traffic control and enforcement of various traffic and parking regulations form an importantpart of the Traffic Enforcer’s function in the safe movement of pedestrians, vehicles, andbicycles on the road. To allow for the safe movement of traffic, the enforcers take appropriateenforcement action to help keep the community in compliance with appropriate traffic laws.Like other countries, the Philippines has laws that require people to wear helmets, fasten seatbelts, prohibit cell phone use, or get drunk while driving in traffic. There are two functions oftraffic law enforcement in the Philippines: To promote citizens' compliance with traffic laws byenforcing laws and regulations to prevent bad situations from happening. Surely, lawenforcement is there to protect the safety of residents when participating in transportation.The following are the findings of the study based on the sub-problems formulated: Sub-problem no. 1 Demographic profile of the respondents in terms of: 1.1 Age, On the part of theTraffic Enforcer, the majority of the respondents are 26 – 33 yrs. Old with a frequency of 14 or70 percent. On the part of the Brgy. Personnel: the majority of the respondents are 26 – 30years old, with a frequency of 16 or 80 percent. 1.2 Sex: On the part of the traffic enforcer, themajority of the respondents are male, with a frequency of 20 or 100 percent, on the part of theBrgy. Personnel: the majority of the respondents are male, with a frequency of 17 or 85percent. 1.3 Civil Status: On the part of the traffic enforcer and barangay respondents, bothgroups got married with a frequency of 20 or 100 percent.
Keywords: Criminology